IMPROVING PERFORMANCE OF MULTIMEDIA DATA DOWNSTREAM WITH PDA IN AN INFRASTRUCTURE NETWORK - HUR, HYE-SUN; HONG, YOUN-SIK (Journal of Mobile Multimedia, 2006)
Assuming that PDAs are used mainly to download data from a stationary server such as a desktop PC in an infrastructure network based on a wireless LAN, an overall performance heavily depends on the performance of such a download with a PDA. Unfortunately, the time taken to receive data from a PC to a PDA is longer than the time taken to send it by 53%. Thus, we measured and analyzed all possible factors that could cause the receiving time of a PDA to be delayed with a test-bed system. There are two crucial factors: TCP window size and file access time of a PDA that can affect the receiving time. The window size of a PDA during the downstream is reduced dramatically to 686 bytes from 32,581 bytes. In addition, because a PDA embeds a flash memory in it, writing data into its flash memory takes 2 times longer than reading data from it. To alleviate these, we propose three distinct remedies: First, to keep the window size at a sender be constant, both the size of a socket send buffer for a desktop PC and the size of a socket receive buffer for a PDA should be increased. Second, to shorten the file access time, the size of an application buffer implemented in an application layer should be set to 8,192 bytes. Finally, an inter-packet delay of a PDA and a desktop PC at an application layer should be adjusted asymmetrically to lower its traffic bottleneck between the heterogeneous terminals.